Enterprise development and women entrepreneurship in the renewable energy independent power producer procurement programme in South Africa - Alcock, Kelly Grace (University of the Witwatersrand, Johannesburg, 2023)
Women entrepreneurs are said to contribute to economic growth and the well-being of societies. The research problem is derived by the pre-historic socio-economic challenges such as a lack of education, financial well-being and socio-cultural aspects which women face in South Africa. This challenges directly impact women entrepreneurs and entrepreneurial activity. The research aims to provide the renewable energy sector with propositions regarding enterprise development and how it can stimulate an entrepreneurial ecosystem. Systemic Entrepreneurship can break the barrier of economic inequality experienced by women in South Africa, especially as they contribute toward the in the informal sector. The purpose is to understand the women entrepreneurship within the REIPPPP and the committed 0,2-0,7% revenue investment to enterprise development. The study aims to review and determine which regulatory frameworks support an entrepreneurial environment to support women entrepreneurs. The study underpins resource-based theory to maintain a competitive advantage and interprets access to human capital, social capital and financial capital by women entrepreneurs. A qualitative research design is applied using semi-structured interview guideline to collect data from industry economic development professionals and women entrepreneurs operating in the renewable energy sector in South Africa. Thematic analysis is the data analysis method used and identifies 21 themes. The findings suggest a positive relationship exists between incentivised procurement and social enterprises in the informal sector and achieving an advantage through collective identity. Similarly, a positive relationship exists between enterprise development and women's entrepreneurship through human capital, social capital and financial capital; community-based development agencies and business sustainability; asset-based community development (ABCD) and entrepreneurship ecosystems; BBBEE and policy and women's empowerment through entrepreneurship. However, criteria are limited due to a lack of transparency, monitoring, evaluation, and a positive relationship between policy, women empowerment, and gender equality
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation, to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Women Entrepreneurship; Enterprise Development; Renewable Energy Independent Power Producer Procurement Programme; Women's Economic Empowerment; Gender Equality; UCTD; SDG-8: Decent work and economic growth